Observations on Bioculture and Medicinal Practices in Akkalkuwa Tehsil (Nandurbar District) In Maharashtra - Khare, S M; Pawar, Shubhangi; Patil, D A (Plantae Scientia, 2022)
An inventory was conducted in a tribal dominated tehsil Akkalkuwa in Nandurbar district of Maharashtra. It was aimed at knowing role of plants in the life of tribal people from the standpoint of concrete and abstract relationship with the ambient plant world. Total 12 angiospermic species belonging to 12 genera and 11 families have a considerable role in their bioculture and healthcare. All these species are used to combat various human afflictions in the form of different recipes. A considerable diversity of diseases is recorded in the area under study. Plant species interwoven with indigenous culture should also be examined for concrete relationship for the welfare of mankind.